Role of complement C1q/C3-CR3 signaling in brain injury after experimental intracerebral hemorrhage and the effect of minocycline treatment - Zheng, Yonghe; Fan, Linfeng; Xia, Siqi; Yang, Qiguo; Zhang, Zhihua; Chen, Huaijun; Zeng, Hanhai; Fu, Xiongjie; Peng, Yucong; Xu, Chaoran; Yu, Kaibo; Liu, Fuyi; et al. (Frontiers in Immunology, 2022)
Aim: The complement cascade is activated and may play an important pathophysiologic role in brain injury after experimental intracerebral hemorrhage (ICH). However, the exact mechanism of specific complement components has not been well studied. This study determined the role of complement C1q/C3-CR3 signaling in brain injury after ICH in mice. The effect of minocycline on C1q/C3-CR3 signaling-induced brain damage was also examined. Methods: There were 3 parts in the study. First, the natural time course of C1q and CR3 expression was determined within 7 days after ICH. Second, mice had an ICH with CR3 agonists LA-1 or vehicle. Behavioral score, neuronal cell death, hematoma volume and oxidative stress response were assessed at 7 days after ICH. Third, the effect of minocycline on C1q/C3-CR3 signaling and brain damage was examined. Results: There were increased numbers of C1q-positive and CR3-positive cells after ICH. Almost all perihematomal C1q-positive and CR3-positive cells were microglia/macrophages. CR3 agonist LA-1 aggravated neurological dysfunction, neuronal cell death and oxidative stress response at day 7 after ICH, as well as enhancing the expression of CD163/HO-1 pathway and accelerating hematoma resolution. Minocycline treatment exerted neuroprotective effects on brain injury following ICH partly due to the inhibition of C1q/C3-CR3 signaling, and that could be reversed by LA-1. Conclusions: The complement C1q/C3-CR3 signaling is upregulated after ICH. The activation of C1q/C3-CR3 signaling by LA-1 aggravates brain injury following ICH. The neuroprotection of minocycline, at least partly, is involved with the repression of the C1q/C3-CR3 signaling pathway.